A randomised controlled trial of group cognitive behavioural therapy for clinical perfectionism - Handley, Alicia Katherine (Curtin University, 2014)
This thesis consisted of two linked studies. The first study examined the relationship between perfectionism and generalised anxiety disorder symptoms in a clinical sample. Perfectionism demonstrated significant associations with pathological worry and a principal diagnosis of generalised anxiety disorder. The second study examined the efficacy of group cognitive behavioural therapy for clinical perfectionism in a clinical sample. This treatment produced significant reductions in perfectionism and psychopathology and significant increases in self-esteem and quality of life.